The Effect of Perceived Quality and User Experience on Repurchase Intention through Customer Satisfaction as an Intervening Variable for inDrive Users in Surabaya - Elizabet, Hena; Nurhadi (Jurnal Manajemen, 2024)
Current business developments are very tight and encourage companies to look for the right marketing strategy so that consumers are interested in repurchasing their products or services. InDrive as an online transportation service has an excellent feature, namely allowing passengers to set their own fares based on their route or destination, able to meet the public’s needs for the availability of desired public transportation. This research aims to determine the influence of perceived quality and user experience on repurchase intention through customer satisfaction as an intervening variable for inDrive online transportation users in Surabaya. The population in this study uses total data from the Surabaya population of 2.87 million people. The sample in this study was 150 respondents, using a quantitative approach. The sampling technique used is non-probability sampling with a purposive sampling method. Partial Least Square analysis was applied to analyze the data tested using the SmartPls 3 application. The results of this study stated that Perceived quality had a positive and significant effect on customer satisfaction, User experience had a positive and significant effect on customer satisfaction, Perceived quality had a positive and significant effect on repurchase intention, User experience had a positive and significant effect on repurchase intention, Customer satisfaction has a positive and significant effect on repurchase intention, Perceived quality has a positive but not significant effect on repurchase intention through customer satisfaction and User Experience has a positive and significant effect on repurchase intention through customer satisfaction.